Move analysis of pharmacy research article discussion sections / Laily Zainal - Zainal, Laily (2015)
In recent years, there has been a growing interest in the study of genre analysis, not only among applied linguists and language teachers for pedagogical reasons but also among research communities. Move analysis is one of the genre-based approaches used to analyse the structure of texts whereby the texts of the chosen corpus were analysed into ‘hierarchical schematic structures or Moves’. One of the genres that have received extensive attention from researchers in move analysis study is Research Article (RA). This is due to its importance in discussing and sharing academic knowledge (Peacock, 2002; Huang, 2014). Therefore, the aim of this work is to analyse the move structure in the discussion section of research articles in the field of Pharmacy. The two objectives of the study is to investigate the extent which the discussion sections in Pharmacy articles can be used with reference to a framework of discussion sections in Applied Linguistics articles and to explore how the writers in Pharmacy construct arguments about the meaning and significance of results in commenting on result moves. In meeting the objectives, twenty discussion sections of Pharmacy research articles have been selected from an international journal and analysed using a schematic structure of Applied Linguistics. Overall, the schematic structure of Applied Linguistics discussion sections can be used to analyse the Pharmacy discussion sections with some modification of the existing framework. All the four moves in the Applied Linguistic framework also occurred in the Pharmacy discussion sections. There are also two additional moves that occurred in the Pharmacy discussion sections. Most of the discussion sections were dominated by Move 3 (Reporting a result) which occurred in 29% of the corpus and Move 4 (Commenting on result), 40% of the corpus. These two moves were used by the Pharmacy writers to construct their argument with regards to their findings. It is hoped that the framework of discussion sections in Pharmacy research article developed in the study could be used as reference for pedagogical reason.